2020
DOI: 10.1002/cbin.11473
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of circPSMC3 sensitizes gefitinib‐resistant esophageal squamous cell carcinoma cells to gefitinib by regulating miR‐10a‐5p/PTEN axis

Abstract: Circular RNAs (circRNAs) has been shown to play an important role in the progression of various cancers. However, the function and underlying mechanisms of circRNAs affecting chemotherapy resistance in esophageal squamous cell carcinoma (ESCC) remain largely unknown. In this study, we used gefitinib‐resistant (GR) ESCC cells to investigate the function of circPSMC3 and clarify the underlying mechanism in chemotherapy resistance in ESCC. The results suggested that circPSMC3 expression was downregulated, but miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…PTEN is an important tumor suppressor gene that encodes a phosphatase protein and resists the PI3K/Akt/mTOR anti-apoptotic pathway as an antagonist ( 33 ). It has been reported that PTEN expression can be promoted by circPSMC3 by decreasing miR-10a-5p levels, which enhances the esophageal squamous cell carcinoma (ESCC) cells towards gefitinib sensitivity ( 34 ).…”
Section: Mechanisms Of Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…PTEN is an important tumor suppressor gene that encodes a phosphatase protein and resists the PI3K/Akt/mTOR anti-apoptotic pathway as an antagonist ( 33 ). It has been reported that PTEN expression can be promoted by circPSMC3 by decreasing miR-10a-5p levels, which enhances the esophageal squamous cell carcinoma (ESCC) cells towards gefitinib sensitivity ( 34 ).…”
Section: Mechanisms Of Drug Resistancementioning
confidence: 99%
“…Moreover, knockdown of circ_0006168 or JMJD1C plays a crucial role in inhibiting cell proliferation, invasion, and migration and promoting apoptosis, which accelerates the taxol sensitivity of Esophageal squamous cell carcinoma (ESCC) in vitro ( 142 ). In contrast, circPSMC3 overexpression inhibits miR-10a-5p expression and increases the sensitivity of ESCC cells to gefitinib ( 34 ).…”
Section: Circrnas and Drug Resistancementioning
confidence: 99%
“…In addition, via regulating miR-194-5p/JMJD1C axis, oncogenic circ_0006168 has been shown to potentiate Taxol resistance in ESCC ( Qu et al, 2021 ). Recently, tumor suppressive circPSMC3, down-regulated in ESCC tissues and gefitinib-resistant (GR) ESCC cells, its overexpression could conquer gefitinib resistance, increase apoptosis rate and cleaved caspase-3 level in GR ESCC cells through modulating the miR-10a-5p/PTEN axis, which provide a promising therapeutic strategy for overcoming gefitinib resistance in ESCC ( Zhu H. et al, 2021 ).…”
Section: Circular Rnas and Drug Resistance In Esophageal Cancermentioning
confidence: 99%
“…For instance, up‐regulated cZNF292 [ 35 ], hsa_circ_0067934 [ 36 ], ciRS‐7 [ 37 ] and circLAPR3, as well as down‐regulated circVRK1 [ 38 ], circLAPR3 [ 39 ] and circLAPR4 [ 40 ], have been reported in OSCC and further validated to regulate the AKT signalling pathway by sponging their respective miRNAs. Down‐regulated circVRK1 [ 38 ], circLAPR4 [ 40 ], circular forkhead box O class (circ‐Foxo3) [ 41 ] and circPSMC3 [ 42 ] all achieved tumour‐suppressive roles by sponging miRNA and subsequently enhancing phosphatase and tensin homolog (PTEN) expression.…”
Section: Circrnamentioning
confidence: 99%
“…circPSMC3 also accelerated apoptosis, with high cleaved caspase‐3 protein expression. The underlying mechanism of circPSMC3 was also explored, showing that circPSMC3 down‐regulates PTEN by acting as an miR‐10a‐5p sponge to suppress the progression of OSCC, meaning that the circPSMC3/miR‐10a‐5p/PTEN axis may be a reliable treatment strategy in the future [ 42 ]. ciRS‐7 was also found to have a regulatory role in starvation or rapamycin‐induced autophagy in OSCC cell lines.…”
Section: Potential Therapeutic Targets For Osccmentioning
confidence: 99%